Optimizing MSME Financial Management through Simple Financial Statement Training - Ivanda Ayu Lestary; Azfa Mutiara Pabulo (Jurnal Pengabdian Masyarakat Bestari, 2024)
This community service program aims to improve the understanding and skills of Micro, Small, and Medium Enterprises (MSMEs) in the preparation of simple financial statements and the preparation of Business Identification Numbers (NIB). Angkringan Pak Owie was chosen as a partner because he faced obstacles in financial management and business legality. The methods used include direct training and mentoring regarding systematic financial recording and steps to make NIB through the Online Single Submission (OSS) platform. Through this activity, partners are able to prepare simple financial statements independently and understand the NIB registration process. The results of this program show that Angkringan Pak Owie has succeeded in registering NIB, so that it has business legality that makes it easier to access capital and opportunities to participate in government programs.